CONDUCTION SENSOR OF LIQUID FLOWING IN DIELECTRIC PIPE - Anatoly Petrovich Popov; Alexander Olegovich Chugulev; Mikhail Romanovich Vinokurov (Advanced Engineering Research)
A fundamentally new design of the contactless inductive sensor for the conduction control of the liquids applied in the chemical, oil-extracting, food, and other industries is offered. The sensor magnetic field is studied using modeling software system Elcut 5.6 Professional. In the course of the investigations, the impact of the excitation current magnitude, its frequency, as well as the diameter of the pipe with conducting liquid, on the magnetic-field pattern is estimated. Thus, the fluid speed was assumed rather low, unaffecting the pickup signal. The studies of the electromagnetic field excited by the alternating current in a cylindrical tube filled with the conductive fluid under its constant parameters are resulted. On the basis of the electromagnetic process simulation results, the recommendations on the optimum parameter ratio dependent on the test medium characteristics are obtained.